Čempresi na Lapadu - Renarić, Dragutin ([S. l.], 1913)
Pejzaž sa čempresima
Signatura d.d. ispod otiska olovkom: Drag. Renarić // 1913.; d.l. ispod otiska olovkom: Čempresi na Lapadu
Digitalna reprodukcija
Pregledano
Keywords: Bakropisi